A Multinomial Asymptotic Representation of Zenga's Discrete Index, its Influence Function and Data-driven Applications - Tchilabalo Abozou Kpanzou; Diam Ba; Gandasor Bonyiri Onesiphore Da; Gane Samb Lo (Revstat Statistical Journal)
In this paper, we consider the Zenga index, one of the most recent inequality indices. We keep the finite-valued original form and address the asymptotic theory. The asymptotic normality is established through a multinomial representation. The Influence function is also given. The results are simulated and applied to Senegalese income data.